The regulatory mechanism of fruit ripening revealed by analyses of direct targets of the tomato MADS-box transcription factor RIPENING INHIBITOR - Fujisawa, Masaki (Landes Bioscience, 2013)
The developmental process of ripening is unique to fleshy fruits and a key factor in fruit quality. The tomato (Solanum lycopersicum) MADS-box transcription factor RIPENING INHIBITOR (RIN), one of the earliest-acting ripening regulators, is required for broad aspects of ripening, including ethylene-dependent and -independent pathways. However, our knowledge of direct RIN target genes has been limited, considering the broad effects of RIN on ripening. In a recent work published in The Plant Cell, we identified 241 direct RIN target genes by chromatin immunoprecipitation coupled with DNA microarray (ChIP-chip) and transcriptome analysis. Functional classification of the targets revealed that RIN participates in the regulation of many biological processes including well-known ripening processes such as climacteric ethylene production and lycopene accumulation. In addition, we found that ethylene is required for the full expression of RIN and several RIN-targeting transcription factor genes at the ripening stage. Here, based on our recently published findings and additional data, we discuss the ripening processes regulated by RIN and the interplay between RIN and ethylene.